2013
DOI: 10.3109/00365548.2013.849816
|View full text |Cite
|
Sign up to set email alerts
|

Herpes simplex virus encephalitis during treatment with etanercept

Abstract: Tumor necrosis factor alpha (TNF-α) inhibitors are widely used for the treatment of various inflammatory conditions. They are associated with an increased risk for infections. We report a case of herpes simplex virus type 1 (HSV-1) encephalitis in a patient receiving etanercept and review the literature on TNF-α and TNF-α inhibitors, and their importance in the pathophysiology of herpes simplex encephalitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The patient was successfully treated with a combination of acyclovir and foscarnet. A patient receiving etanercept (i.e., a fusion protein made of the extracellular domain of human TNF receptor 2 and the Fc end of human IgG 1 ) developed HSE (173). MRI scans showed lesions in the right fronto-temporoparietal region with the presence of edema.…”
Section: Occurrence Of Hse After Immunomodulatory Therapymentioning
confidence: 99%
“…The patient was successfully treated with a combination of acyclovir and foscarnet. A patient receiving etanercept (i.e., a fusion protein made of the extracellular domain of human TNF receptor 2 and the Fc end of human IgG 1 ) developed HSE (173). MRI scans showed lesions in the right fronto-temporoparietal region with the presence of edema.…”
Section: Occurrence Of Hse After Immunomodulatory Therapymentioning
confidence: 99%
“…Herpes encephalitis in immunocompromised patients, mainly in relation to TNF-alpha inhibitors such as infliximab, is reported in the literature in some case reports [ 5 , 6 , 7 ]. Among these, 5 cases are described of patients with TNF-alpha inhibitor therapy and herpes encephalitis.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the Th1/Th17 cells in the periphery of RA patients are reduced, and Tregs are significantly increased after rhTNFR:Fc therapy [ 32 ]. In recent years, there have been many documents reported the multiple side effects accompanied with anti-TNF-α therapies, such as the increased risk of severe viral and bacterium infection [ 33 , 34 ], anaphylaxis [ 35 ], and tumor [ 36 ]. Additionally, their considerable costs still limit their widespread utilization.…”
Section: Discussionmentioning
confidence: 99%